Fraud Pentagon in Fraudulent Financial Statements - Dea Arme Tiara Harahap; Poppy Sofia Koeswayo; Cahya Irawady (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to examine the fraud pentagon, namely the effect of pressure, opportunity, rationalization, ability and arrogance in fraudulent financial statements. This type of research is descriptive verification which is causality in nature. The unit of analysis in the research is BUMN listed on the Indonesia Stock Exchange in 2015-2019. This research data is a sample with purposive sampling technique and obtained 30 data samples. And analyzed by logistic regression analysis techniques. The results of this study show partially the effectiveness of proxy control of opportunity to influence financial statement fraud. Meanwhile, financial pressure (ROA), rationalization (auditor change), and arrogance (share ownership) have no effect on fraudulent financial statements